Interpretasi Tahanan Jenis Dua Dimensi Konfigurasi Wenner untuk Menentukan Struktur Bawah Permukaan di Kota Samarinda Provinsi Kalimantan Timur - Fadlan Al Anshar; Noor Fauzi Isniarno; Dudi Nasrudi Usman (Bandung Conference Series: Mining Engineering, 2023)
Abstract. Judging from the regional geological map on the Samarinda sheet, it was found that in the study area there was a very complex structure. Geolistics is a method that can analyze subsurface structures with resistivity values. To identify subsurface conditions, it is necessary to model the results of measurements to strengthen interpretation with geological maps. Geoelectrical measurements were carried out using a 2-dimensional Wenner configuration NeoResist tool with the same distance between electrodes, which will produce an apparent resistivity value, resistivity resulting from software processing, and an apparent resistivity cross-section. Measurements were carried out in four tracks on fairly steep topographical conditions with a spacing of 10 meters between electrodes and a stretch of 400 meters. Acquisition and interpretation of measurement results obtained the lithology of minerals, including sandstone and claystone, and encountered geological structures in geoelectrical measurements. The results of the measurements obtained an indication of the structure on tracks 1, 3, and 4 and an anomaly in the resistivity value because there is a resistivity value that decreases and forms like a structure. On the cross section of track 1, there is a change in resistivity that is indicated to be affected by a rising fault in the western part of the geological map; on track 3, it is found that there is a resistivity filling like a fracture; on track 4, it gets resistivity like a fracture that is almost upright; and it is indicated that in that area, the change results from the influence of trajectory 1. This indication is strengthened by the location of the research area, which is surrounded by a complex structure. Abstrak. Ditinjau dari peta geologi regional pada lembar samarinda dijumpai bahwa pada daerah penelitian terdapat adanya struktur yang sangat komplek. Geolistik salah satu metode yang dapat menganalisis strukur bawah permukaan dengan nilai resisitivity. Untuk mengidentifikasi kondisi bawah permukaan di perlukan pemodelan hasil dari pengukuran untuk memperkuat interptretasi dengan peta geologi. Pengukuran geolistrik dilakukan menggunakan alat NeoResist konfigurasi wenner 2 dimensi dengan jarak antar elektroda yang sama akan menghasilkan nilai tahanan jenis semu, tahanan jenis hasil dari pengolahan software, Penampang apparent resistivity. Pengukuran dilakukan sebanyak 4 lintasan pada kondisi topografi yang cukup curam dengan jarak antar elektroda 10 meter dan bentangan sepanjang 400 meter. Akuisisi dan interpretasi data hasil pengukuran didapatkan litologi bahan galian diantaranya adalah batupasir dan batulempung, serta di jumpai adanya struktur geologi dalam pengukuran geolistrik. Hasil dari pengukuran didapatkan adanya indikasi struktur pada lintasan 1, 3 dan 4 dan didapatkan anomali pada nilai resistivity di karenakan terdapat nilai resistivity yang menunjam serta membentuk seperti struktur. Pada penampang lintasan 1 terdapat adanya perubahan resistivity yang diindikasikan terdampak oleh sesar naik pada bagian barat pada peta geologi, pada lintasan 3 didapatkan adanya resistivity yang mengisi seperti rekahan, pada lintasan 4 di dapatkan resistivity seperti rekahan yang hampir tegak dan diindikasikan bahwa pada daerah tersebut hasil dari pengaruh lintasan 1. Indikasi tersebut perkuat dengan lokasi daerah penelitian di kelilingi dengan struktur yang kompleks.